Relationship between dietary factors and recurrent aphthous stomatitis in China: a cross-sectional study. Issue 5 (May 2021) - Xu, Kaiyuan; Zhou, Chongchong; Huang, Fan; Duan, Ning; Wang, Yanyi; Zheng, Lichun; Wang, Xiang; Wang, Wenmei
Objective: Recurrent aphthous stomatitis (RAS), a common oral mucosal disorder characterized by chronic, inflammatory, and ovoid ulcers, has a complex etiology. The purpose of the study was to investigate the specific dietary factors influencing the prevalence of RAS. Methods: A total of 754 participants aged 18 to 59 years were enrolled in this descriptive cross-sectional study. An anonymous questionnaire was adopted to investigate the distribution of RAS, dietary factors, self-reported trigger factors, and therapeutic methods. Results: Among all participants, the prevalence rate of RAS was 21.4%. Univariable analysis showed that fruit, dairy products, vegetables, and water, but not fried foods, fermented foods, spicy foods, and eggs, were preventive factors against RAS. After adjusting for age and sex, multivariable regression analysis suggested that fruit (adjusted odds ratio [aOR] = 0.430, 95% confidence interval [CI] = 0.218–0.847) and water (aOR = 0.294, 95% CI = 0.119–0.726) were protective factors against RAS. Conclusion: This study found that the consumption of fruit and water was negatively associated with RAS. These results imply a potential adjunctive and complementary role of food in RAS treatment and some feasible means of RAS prevention.